2019
DOI: 10.1002/jlb.3mir1118-414rr
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles and danger signals: Oral delivery vehicles as potential disruptors of intestinal barrier homeostasis

Abstract: Gut immune system homeostasis involves diverse structural interactions among resident microbiota, the protective mucus layer, and a variety of cells (intestinal epithelial, lymphoid, and myeloid). Due to the substantial surface area in direct contact with an "external" environment and the diversity of xenobiotic, abiotic, and self-interactions coordinating to maintain gut homeostasis, there is enhanced potential for the generation of endogenous danger signals when this balance is lost. Here, we focus on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 89 publications
(148 reference statements)
1
38
0
Order By: Relevance
“…125 After oral intake, NPs accumulate on the surfaces of intestinal epithelial cells, M cells, and Peyer patches. 126 They are translocated through the intestinal epithelial barrier either via endocytosis by M cells (TiO 2 ) or by increasing the cell leakage secondary to disruption of the cell membrane integrity (SiO 2 , TiO 2 , and ZnO) or by phagocytosis by macrophages. 126 Furthermore, paracellular permeability of the intestinal barrier has been shown to increase after the administration of TiO 2 -NPs.…”
Section: Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…125 After oral intake, NPs accumulate on the surfaces of intestinal epithelial cells, M cells, and Peyer patches. 126 They are translocated through the intestinal epithelial barrier either via endocytosis by M cells (TiO 2 ) or by increasing the cell leakage secondary to disruption of the cell membrane integrity (SiO 2 , TiO 2 , and ZnO) or by phagocytosis by macrophages. 126 Furthermore, paracellular permeability of the intestinal barrier has been shown to increase after the administration of TiO 2 -NPs.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…126 They are translocated through the intestinal epithelial barrier either via endocytosis by M cells (TiO 2 ) or by increasing the cell leakage secondary to disruption of the cell membrane integrity (SiO 2 , TiO 2 , and ZnO) or by phagocytosis by macrophages. 126 Furthermore, paracellular permeability of the intestinal barrier has been shown to increase after the administration of TiO 2 -NPs. Both in vitro and in vivo studies have demonstrated that NPs induce ROS following internalization.…”
Section: Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are substantial data reporting that pollutants such as cigarette smoke, particulate matter, diesel exhaust, ozone, nanoparticles, microplastic, detergents, and cleaning agents and chemicals in household substances damage the epithelial barrier. 37,38,[66][67][68][69][70][71][72][73][74][75] After the opening of the barrier, a local inflammation starts, and the tissue may become more vulnerable to inflammatory and tissue destructive effects of pollution. Most of these pollutants indicate synergistic effects, and the area is fully open for future research.…”
Section: Epithelium and The Environmentmentioning
confidence: 99%
“…The "danger signals" would act on DCs, in aseptic conditions, in a similar manner to the microbial molecular patterns. Therefore, the question to be addressed is whether engineered NP could act as danger signals, as previously suggested for ultrafine or diesel exhaust particles [14] and could be considered as NAMPs (nanoparticle-associated molecular patterns) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%